THE EFFECT OF TEST TUBE STERILIZATION FROM SERUM LIPEMIC AGAINST LEVELS OF TRIGLYCERIDE GPO-PAP METHOD - Fitri Fadhilah; Ana Bina Sari; Astika Aprilianti (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
In terms of analytic factors, it is important to define acceptable levels of common interferences, such as lipemia or hemolysis. For triglyceride, the laboratory technician must define whether samples with excess lipemia will be included in the study; this depends, in part, on whether the interferences affect the methods. In most laboratories, glass or plastic that is in direct contact associated with bio hazardous material is usually disposable. If not, it must be decontaminated according to appropriate protocols. Immediately rinsing glass or plastic supplies after use, followed by washing with a powder or liquid detergent designed for cleaning laboratory supplies and several distilled water rinses, may be insufficient. To ensure that all remaining fat from lipemic serum that attached to the tube wall has been removed, then the sterilization process is carried out so that a sterile tube is obtained. The purpose of this study is to determine the effect of test tube sterilization from serum lipemic against levels of triglyceride GPO-PAP (Glycerol-3-phosphate oxidase-p-aminophenazone) examination. This research method was a laboratory experiment. We used 8 times repetition with tubes used first are given liquid fat and cleaned by sterilization, washed with surfactant and washed with water only. By using statistical tests ANOVA obtained of this study showed results p>0.05 which is mean the treatment that used did not show a significant difference in the treatment of ordinary water-washed tubes with sterilized tubes and surfactant washed tubes. The conclusion of this study is cleaning of the test tube with the sterilization method is recommended because to avoiding the fear of remaining pollutants that can affect the results, It can also minimize the life of bacteria and viruses from the sample to be examined. However, if the sterilization method is difficult to do because of limited equipment and so on, the use of surfactants and the correct method of cleaning the tube is enough to remove impurities such as fat.